A novel synchronization algorithm for OFDM system based on training sequence added scramble code - Zongshan Pang; Xiaomin Li (2009 IEEE International Conference on Communication Technology and Applications, 2009)
Synchronization is key technology of OFDM system. SC algorithm adopts training sequence presented by Schmidl and Cox. It's estimation of timing and frequency offset is more precise. But SC algorithm has platform when estimating the timing. In this paper, a novel method is presented aimed to solve SC's platform problem. A PN are used to scramble the training sequence in transmitter. In the receiver, training sequence could be recovered by the PN only at the right position of symbol synchronization. This method solves the time platform problem of SC algorithm, enhances the performance of SC algorithm.